Comparison of the Effectiveness of Acceptance and Commitment Therapy With and Without Compassion on the Psychological Pain Indicators of Patients With Chronic Tension Headaches - Kavian, Mina; Shahabizadeh, Fatemeh; Jafar Tabatabaei, Samaneh Sada (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to evaluate the effectiveness of Acceptance and Commitment Therapy (ACT) with and without compassion on the psychological pain indicators of patients.Methods and Materials: This quasi-experimental study included a pretest-posttest design with a control group and a three-month follow-up. From the population of patients (chronic tension headaches) who visited the Senabad Neurology Center in Mashhad during the first quarter of 2023, 45 individuals meeting the inclusion criteria were selected through convenience sampling and randomly assigned to three groups (two experimental groups and one control group). All participants completed the research questionnaires before and after the group therapies. Additionally, the questionnaires were completed again by the participants after the three-month follow-up period.Findings: The results indicate that Acceptance and Commitment Therapy, both with and without compassion, had significantly different effects on psychological pain indicators. The effectiveness of ACT with compassion in improving psychological pain indicators was significantly greater than ACT without compassion.Conclusion: Acceptance and Commitment Therapy, with or without compassion, can be used to manage and control certain symptoms and signs of chronic tension headaches, such as enhancing and restoring psychological pain indicators in affected individuals.